Monsoon-driven biogeochemical dynamics in an equatorial shelf sea: Time-series observations in the Singapore Strait. (5th June 2022) - Martin, Patrick; Moynihan, Molly A.; Chen, Shuang; Woo, Oon Yee; Zhou, Yongli; Nichols, Robert S.; Chang, Kristy Y.W.; Tan, Ashleen S.Y.; Chen, Ying-Hsuan; Ren, Haojia; Chen, Mengli
Abstract: Coastal tropical waters are experiencing rapid increases in anthropogenic pressures, yet coastal biogeochemical dynamics in the tropics are poorly studied. We present a multi-year biogeochemical time series from the Singapore Strait in Southeast Asia's Sunda Shelf Sea. Despite being highly urbanised and a major shipping port, the strait harbours numerous biologically diverse habitats and is a valuable system for understanding how tropical marine ecosystems respond to anthropogenic pressures. We observed strong seasonality driven by the semi-annual reversal of ocean currents: dissolved inorganic nitrogen (DIN) and phosphorus varied from ≤0.05 μmol l −1 during the intermonsoons to ≥4 μmol l −1 and ≥0.25 μmol l −1, respectively, during the southwest monsoon. Si(OH)4 exceeded DIN year-round. Based on nutrient concentrations, their relationships to salinity and coloured dissolved organic matter, and the isotopic composition of NOx −, we infer that terrestrial input from peatlands is the main nutrient source. This input delivered dissolved organic carbon (DOC) and nitrogen, but was notably depleted in dissolved organic phosphorus. In contrast, particulate organic matter showed little seasonality, and the δ 13 C of particulate organic carbon (−21.0 ± 1.5‰) is consistent with a primarily autochthonous origin. The seasonal pattern of the diel changes in dissolved O2 suggests that light availability controls primary productivity more than nutrient concentrations. However, diel changes in pH were greater during the southwest monsoon, when remineralisation of terrestrial DOC lowers the seawater buffer capacity. We conclude that terrestrial input results in mesotrophic conditions, and that the strait might undergo further eutrophication if nutrient inputs increase during seasons when light availability is high. Moreover, the remineralisation of terrestrial DOC within the Sunda Shelf Sea may enhance future ocean acidification. Graphical abstract: Image 1 Highlights: Multi-year time-series data show strong monsoonal seasonality. River input from regional peatlands is a major driver of seasonal variation. Light limitation likely modulates phytoplankton response to nutrient input. Lower buffer capacity from peatland carbon remineralisation raises diel pH variation.